2014
DOI: 10.1002/jhm.2296
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and in-hospital asthma resource utilization

Abstract: OBJECTIVE: To examine the relationship between pediatric obesity and inpatient length of stay (LOS), resource utilization, readmission rates, and total billed charges for inhospital status asthmaticus. DESIGN/METHODS:We conducted a cross-sectional study of patients 5 to 17 years old hospitalized with status asthmaticus to 1 free-standing children's hospital system over 12 months. Only hospitalized patients initially treated in the hospital's emergency department were included to ensure all therapies/charges we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
2
7
1
1
Order By: Relevance
“…Our results may be more reliable because we calculated BMI percentile rather than using administrative data, which has been shown to be inaccurate in identifying obese patients. 36,37 In our study, billing data captured only 4% of children as obese and none as overweight. It is also possible that associations between obesity and poor asthma hospitalization outcomes identified by previous studies were confounded by asthma severity, which was controlled for in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results may be more reliable because we calculated BMI percentile rather than using administrative data, which has been shown to be inaccurate in identifying obese patients. 36,37 In our study, billing data captured only 4% of children as obese and none as overweight. It is also possible that associations between obesity and poor asthma hospitalization outcomes identified by previous studies were confounded by asthma severity, which was controlled for in our study.…”
Section: Discussionmentioning
confidence: 93%
“…12,13 Although a smaller study assessing health care costs for multiple diagnoses in obese children from urban communities found obesity was associated with increased costs for asthma admissions, another assessing for hospitalization outcomes found that obesity was not associated with measures of resource utilization. 14,15 We used chart review and direct calculation of BMI percentile rather than diagnostic obesity codes to more accurately assess a range of hospitalization outcomes (LOS, charges, ICU stay, repeat admissions, and subsequent ED visits). This method was chosen to avoid misclassification of obesity status that may occur with administrative data and because it allowed us to control for variables not captured by administrative data that can affect admission outcomes (such as asthma severity and comorbidities).…”
Section: Resultsmentioning
confidence: 99%
“…Although cost of care and rate of readmission or return to the hospital are important issues in health care, a recent study by Bettenhausen et al 17 did not show a relationship between BMI and resource utilization or cost of care; however, Aragona et al 36 did show that obese patients were more likely to have return visits.…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9][12][13][14] However, there is inconsistency in the literature, and some studies have not found that higher BMI percentile predicts admission or effects health care outcomes in children with asthma. [15][16][17] There remains a lack of data on the prevalence of overweight and obesity among children with asthma in the inpatient setting and, more importantly, a lack of information about the clinical practices related to this population.…”
mentioning
confidence: 99%
“…), многие из которых синтезируются и секретиру-ются клетками жировой (адипозной) ткани [4,5] и поэтому названы адипокинами, включая IL-6, IL-10, эотаксин, фактор некроза опухоли α, трансфор-мируемый фактор роста β1, C-реактивный протеин, лептин и адипонектин. Наконец, было идентифи-цировано, что идентичные локусы генома человека отвечают как за БА, так и за ожирение [6][7][8][9][10][11].…”
Section: ключевые слова: бронхиальная астма избыточная масса тела сunclassified